An evolutionary approach to regional housing resilience: the role of agency and the 'epistemic community'. Issue 7 (9th August 2019) - Lee, Peter
Abstract: The equilibrium model of resilience following shock has been highly critiqued as it implies status quo and no change in underlying power structures. This article fills a gap in the resilience literature as it applies to planning for housing by discussing the role of agency in contributing to the adaptive capacity of regions in responding shock events. A central tenet of the article is how agents can be the shock in slow-burn events. A case study of the development of regional strategic housing market assessments in an English region in the run-up to and during the global financial crisis illustrates how the concept of the epistemic community applies to planning for housing across scales. As resilience will increasingly drive global investments over the next century the aim of the article is to move away from rigid and conservative expressions of resilience to a more evolutionary approach relevant to regional housing systems.